2021
DOI: 10.21608/ajps.2021.187828
|View full text |Cite
|
Sign up to set email alerts
|

Monosodium Glutamate Safety, Neurotoxicity and Some Recent Studies

Abstract: Monosodium glutamate (MSG) is a worldwide flavor enhancer. Despite controversy surrounding the safety of MSG, it is still consumed in large amounts. This review provides a better understanding of the molecular mechanism of MSG induced neurotoxicity including the different ways of glutamate regulation in brain and umami taste signaling pathway. In addition, this review summarizes the history of MSG discovery and synthesis, products and natural food containing MSG, details of MSG safety and toxicity with limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 77 publications
0
8
0
1
Order By: Relevance
“…Мутації генів у своє чергу потенційно можуть спричинити розвиток патологічних станів, метаболічних порушень, неоплазій і неврологічних дефектів [13], які можуть мати місце і в наступних поколіннях [14]. Сучасні дослідження довели, що глутамат натрію чинить токсичний вплив на слинні залози [15,16,17], тканини зубів [10], печінки [19,20], підшлункової залози [21,22], товстої кишки [23,24], спричиняє пошкодження статевої системи [25,26] [27]. Знаходимо дані і щодо причетності глутамату натрію до розвитку неспецифічного виразкового коліту або хвороби Крона, це пояснюється досить частим вживанням Е 621 у складі багатих на жири продуктів, що призводить до порушення мікробіому кищечника та, як наслідок, виникнення запальних процесів [23].…”
Section: актуальні проблеми сучасної медициниunclassified
“…Мутації генів у своє чергу потенційно можуть спричинити розвиток патологічних станів, метаболічних порушень, неоплазій і неврологічних дефектів [13], які можуть мати місце і в наступних поколіннях [14]. Сучасні дослідження довели, що глутамат натрію чинить токсичний вплив на слинні залози [15,16,17], тканини зубів [10], печінки [19,20], підшлункової залози [21,22], товстої кишки [23,24], спричиняє пошкодження статевої системи [25,26] [27]. Знаходимо дані і щодо причетності глутамату натрію до розвитку неспецифічного виразкового коліту або хвороби Крона, це пояснюється досить частим вживанням Е 621 у складі багатих на жири продуктів, що призводить до порушення мікробіому кищечника та, як наслідок, виникнення запальних процесів [23].…”
Section: актуальні проблеми сучасної медициниunclassified
“…They either enhance taste, texture, color, or durability of food (1). Monosodium Glutamate (MSG) is a popular flavor enhancer frequently used in food industry (2). Aside from being used as a food additive, it is also naturally found in many types of food such as cow milk, eggs, cheese, tomatoes, almonds, apple, onion, potato, carrot, garlic and walnut (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged glutamate excitotoxicity leads to oxidative stress mainly through upregulation of Reactive Oxygen Species (ROS) generation and decrease in the antioxidant defense pathways which make the cell more vulnerable to damage and death. Recent studies reported that the oxidative stress status induced by MSG consumption may affect multiple organs such as the brain, liver, kidney, and testis and cause their damage (2,(6)(7)(8). Oxidative stress induced by MSG may be prevented by administration of antioxidants Alexandria Dental Journal.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive calcium entry into cells causes mitochondrial dysfunction, which raises intracellular nitric oxide levels and promotes cell apoptosis [5]. In vitro, excitotoxicity and cystine transport inhibition‐related oxidative stresses have been considered two important mechanisms of glutamate neurotoxicity [6]. If left untreated, excessive glutamate exposure results in membrane depolarization, which can lead to cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive calcium entry into cells causes mitochondrial dysfunction, which raises intracellular nitric oxide levels and promotes cell apoptosis [5]. In vitro, excitotoxicity and cystine transport inhibition-related oxidative stresses have been considered two important mechanisms of glutamate neurotoxicity [6]. If left untreated, excessive glutamate exposure results in membrane depolarization, which can lead to Abbreviations: FBS, fetal bovine serum; GMP, guanosine monophosphate; nNOS, neuronal nitric oxide synthase; NO, nitric oxide; ROS, reactive oxygen species; sGC, soluble guanylate cyclase; TAS, total antioxidant status; TOS, total oxidant status.…”
mentioning
confidence: 99%